2008
DOI: 10.3748/wjg.14.1997
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of percutaneous ethanol injection therapy for minimum-sized hepatocellular carcinoma

Abstract: Treatment with PEI is best indicated for patients with HCC < 15 mm in Child-Pugh class A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…It was reported that DMSO as an anti-oxidant agents performed a good anti-tumor activity by inducing changes in specific gene expression (Bilir et al, 2004;Liu et al, 2007;Sharma et al, 1998;Yoshikawa et al, 1993). The toxicity of ethanol on the tumor cells was also reported (Datta et al, 1990;Fronio et al, 2005;Taniguchi et al, 2008). In addition, at the early stage of tumor growth, the tumor cells might be tender to the organic solvent.…”
Section: In Vivo Anti-tumor Activity Evaluationmentioning
confidence: 75%
“…It was reported that DMSO as an anti-oxidant agents performed a good anti-tumor activity by inducing changes in specific gene expression (Bilir et al, 2004;Liu et al, 2007;Sharma et al, 1998;Yoshikawa et al, 1993). The toxicity of ethanol on the tumor cells was also reported (Datta et al, 1990;Fronio et al, 2005;Taniguchi et al, 2008). In addition, at the early stage of tumor growth, the tumor cells might be tender to the organic solvent.…”
Section: In Vivo Anti-tumor Activity Evaluationmentioning
confidence: 75%
“…Thus, in recent years, some nonsurgical treatments such as percutaneous ethanol injection (PEI) [6,7] and radiofrequency thermal ablation (RFTA) [8,9] were developed. The aim of these therapies is to treat patients who are not candidates for resection due to advanced age, underlying diseases, multinodular HCCs or unfavorable locations, such as tumours too close to vascular and biliary structures [6,[8][9][10][11][12], by means of a complete coagulation tumor necrosis. Furthermore, surgical resection in cirrhotic patients with impaired liver function leads to a high risk of hepatic failure and postsurgical recurrences of preoperatively undetected nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Pertanto nel corso degli ultimi anni sono stati proposti alcuni tipi di trattamento percutaneo non chirurgico, come l'iniezione percutanea di etanolo (PEI) [6,7] e la termoablazione con radiofrequenza (RFTA) [8,9]. Lo scopo di tali trattamenti è di poter trattare, mediante il raggiungimento di una completa necrosi coagulativa del tessuto tumorale, i pazienti considerati inoperabili per l'età avanzata, per comorbilità, per caratteristiche proprie del tumore, come la stretta adiacenza a strutture vascolari e biliari o per la multifocalità delle lesioni [6,[8][9][10][11][12]. Inoltre, la resezione nei pazienti cirrotici con ridotta funzionalità epatica conduce ad un significativo rischio di insufficienza epatica post-chirurgica e di recidive post-chirurgiche per foci tumorali non diagnosticati all'imaging pre-operatorio.…”
Section: Introductionunclassified
“…In general, RFA is superior to PEI for tumor control. PEI, however, can almost totally ablate HCCs 11-15 mm in diameter [20], although the demonstration of complete necrosis by percutaneous core biopsy would not confirm complete tumor necrosis. In conclusion, from the viewpoint of safety, feasibility, and tumor control, we administered PEI, instead of RFA, for well-differentiated HCCs smaller than 15 mm in diameter, located near the bile ducts, the gall bladders, and the diaphragm.…”
Section: Discussionmentioning
confidence: 91%